2017
DOI: 10.1039/c7cc04055e
|View full text |Cite
|
Sign up to set email alerts
|

A bioconjugate leveraging xenoreactive antibodies to alleviate cocaine-induced behavior

Abstract: A method for potentiating the response to an anti-cocaine vaccine by leveraging xenoreactive antibodies against the carbohydrate epitope Galα1,3-Gal (GAL) was found to result in a highly specific anti-cocaine response that was able to significantly attenuate cocaine-induced locomotion at 20 mg/kg with superior efficacy compared to a standard conjugate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Within the GC, CD4 + T helper (Th) cells will also differentiate into Th 1 , Th 2 , Th 17 , T follicular helper (T fh ), and GC-T fh subsets which coordinate B cell responses to different antigens 27,28 . In this context, B and T cell responses to vaccines can be shaped by the incorporation of adjuvants to achieve successful immunization 29,30 . Pre-clinical studies have already shown that the efficacy of vaccines against SUD is enhanced by adjuvants such as aluminum salts (alum) and toll-like receptor 4 (TLR4) or TLR9 agonists [31][32][33][34] .…”
Section: Introductionmentioning
confidence: 99%
“…Within the GC, CD4 + T helper (Th) cells will also differentiate into Th 1 , Th 2 , Th 17 , T follicular helper (T fh ), and GC-T fh subsets which coordinate B cell responses to different antigens 27,28 . In this context, B and T cell responses to vaccines can be shaped by the incorporation of adjuvants to achieve successful immunization 29,30 . Pre-clinical studies have already shown that the efficacy of vaccines against SUD is enhanced by adjuvants such as aluminum salts (alum) and toll-like receptor 4 (TLR4) or TLR9 agonists [31][32][33][34] .…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced antigen uptake and presentation by antigen-presenting cells was achieved by targeting the Fcγ receptor (FcγR) stimulating the release of cytokines for the recruitment of effector cells (e.g., CD4 + T cells). In this study, anti-cocaine vaccines GNE -OVA-GAL (and GNE -TT-GAL; Table ) formulated with alhydrogel effectively produced a viable anti-cocaine response . This xenoreactive antibody vaccination strategy led to an antibody response with higher affinity for cocaine that significantly attenuated cocaine-induced locomotion.…”
Section: Anti-cocaine Vaccinesmentioning
confidence: 99%
“…Janda and co-workers devised a method for enhancing the response to cocaine haptens through conjugation of a carbohydrate epitope (e.g., Galα1,3-Gal, GAL), leading to a highly specific anti-cocaine vaccine that significantly attenuated cocaine-induced locomotion compared to the hapten−carrier protein alone. 51 Enhanced antigen uptake and presentation by antigen-presenting cells was achieved by targeting the Fcγ receptor (FcγR) stimulating the release of cytokines for the recruitment of effector cells (e.g., CD4 + T cells). In this study, anti-cocaine vaccines GNE-OVA-GAL (and GNE-TT-GAL; Table 1) formulated with alhydrogel effectively produced a viable anti-cocaine response.…”
Section: Pre-clinical Advances Inmentioning
confidence: 99%
“…Antidrug vaccines targeting multiple, structurally distinct species are not common and have utilized two tactics: 1) mixing two individual vaccines together (admixture vaccine) [910]; or 2) successive conjugation steps of one hapten and then the second to a carrier protein [1112]. To specifically address the escalating incidence of fentanyl-contamination in heroin, we investigated the efficacy of an admixture of individual heroin and fentanyl conjugate vaccines against challenges of 10–20% fentanyl in heroin [1314].…”
Section: Introductionmentioning
confidence: 99%